Constitutive Equation Determination and Dynamic Numerical Modelling of the Compression Deformation of Concrete - Saatcı, Selçuk; Seven, Semih Berk; Güden, Mustafa; Çankaya, M. Alper; Taşdemirci, Alper; Uysal, Çetin; Taşdemirci, Alper; Saatci, Selçuk; Güden, Mustafa (Wiley, 2021)
The dynamic compression deformation of an in-house cast concrete (average aggregate size of 2-2.5 mm) was modelled using the finite element (FE), element-free Galerkin (EFG) and smooth particle Galerkin (SPG) methods to determine their capabilities of capturing the dynamic deformation. The numerical results were validated with those of the experimental split Hopkinson pressure bar tests. Both EFG and FE methods overestimated the failure stress and strain values, while the SPG method underestimated the peak stress. SPG showed similar load capacity profile with the experiment. At initial stages of the loading, all methods present similar behaviour. Nonetheless, as the loading continues, the SPG method predicts closer agreement of deformation profile and force histories. The increase in strength at high strain rate was due to both the rate sensitivity and lateral inertia caused by the confinement effect. The inertia effect of the material especially is effective at lower strain values and the strain rate sensitivity of the concrete becomes significant at higher strain values.
Keywords: Concretes; LS-DYNA; Pulse shaper; Quartz crystal; Split Hopkinson Pressure Bar